Technetium Colloidal Behavior in Deionized Water System under Simulated HLW Geological Disposal Condition - SHAO Yanjiang;WANG Bo;ZHOU Duo;CHEN Xi;FANG Sheng;XU Yuwei;XU Qiangwei;LIU Chen;BAO Liangjin;LONG Haoqi;XIAN Liang (Yuanzineng kexue jishu, 2023)
99Tc is a key radionuclide in the safety case of deep geological disposal of high-level radioactive waste (HLW) due to its long half-life of 2.13×105 years and high yield in nuclear reactors. The formation of technetium colloid in groundwater was believed to play a potential important role on its migration and transport with ground-water to biosphere under deep geological disposal conditions. In this paper, the membrane filtration experimental method was established firstly for the study of the colloidal behavior of technetium in aqueous solutions. All experiments were performed in an argon glove box to maintain the anaerobic conditions (O2 concentrations lower than 5 ppm) which will be expected in the HLW repository and initial technetium concentrations in the range from 10-9 mol/L to 10-5 mol/L, and liquid scintillation spectrophotometry was used to determine 99Tc. It is found that pH value and ionic strength have no significant effect on the liquid scintillation determination of 99Tc, and the filter has no obvious adsorption behavior for different oxidation states of technetium (Tc(Ⅳ) and Tc(Ⅶ)). The experimental studies of technetium colloidal behavior in deionized water system were conducted by using this experimental method. The results indicate that Tc(Ⅶ) has no significantly colloidal behavior even under anaerobic conditions due to its low hydrolysis ability, and can exist stably in the system for a long time, therefore it is a potentially higher mobile species. As Tc(Ⅳ) is trend to hydrolyze to form oxic polymers easily, which then aggregate immediately to form the intrinsic colloids over a wide ranging of pH values from 4 to 11 under the anaerobic conditions. Moreover, it is found that the Tc(Ⅶ) intrinsic colloid would exist stably during the experimental period of 398 days in the pH range of 4-11, and its concentrations may be several times or even one order of magnitude higher than the Tc(Ⅳ) presented as the ionic form. These results seem mean that the formation of Tc(Ⅶ) colloid may enhance the migration capacity of Tc(Ⅳ) which is considered to be relatively immobile, then potentially facilitating transport of Tc(Ⅳ) under geological disposal conditions. But the next experimental results demonstrate that with the increasing of the ionic strength, the Tc(Ⅳ) colloid would aggregate into large particles even continue to form precipitation. This experimental results illustrate that higher ionic strength in aqueous systems may eliminate the dangerous of Tc(Ⅳ) transfer to biosphere with groundwater in the form of intrinsic colloid. The effect of technetium colloidal on its migration behavior needs to be take into account, and some important formation mechanism of technetium colloidal also needs to be clarified and confirmed. Therefore, it is necessary to carry out more researches on radionuclide colloids in the research and development projects of geological disposal of HLW in China.